2023
DOI: 10.3390/biomedicines11061682
|View full text |Cite
|
Sign up to set email alerts
|

The Central Fluid Percussion Brain Injury in a Gyrencephalic Pig Brain: Scalable Diffuse Injury and Tissue Viability for Glial Cell Immunolabeling following Long-Term Refrigerated Storage

Abstract: Traumatic brain injury (TBI) affects millions of people annually; however, our knowledge of the diffuse pathologies associated with TBI is limited. As diffuse pathologies, including axonal injury and neuroinflammatory changes, are difficult to visualize in the clinical population, animal models are used. In the current study, we used the central fluid percussion injury (CFPI) model in a micro pig to study the potential scalability of these diffuse pathologies in a gyrencephalic brain of a species with inflamma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…There are several different TBI models that utilize gyrencephalic subjects such as ferrets (Krieg et al., 2023; Schwerin et al., 2017, 2023; Whyte et al., 2019), swine (Kinder et al., 2019; Lafrenaye et al., 2015; Pavlichenko & Lafrenaye, 2023), sheep (Sharkey et al., 2023), and non‐human primates, among other species (Osier & Dixon, 2016; Vink, 2018). Common models that use gyrencephalic subjects are variations of CCI (Schwerin et al., 2017), FPI (Brodhun et al., 2001; Pavlichenko & Lafrenaye, 2023), and the CHIMERA (Krieg et al., 2023; Schwerin et al., 2023; Whyte et al., 2019). Further, another widely used large animal model is an acceleration injury model that produces DAI (Vink, 2018).…”
Section: Beyond the Rodent: Gyrencephalic Models Of Tbimentioning
confidence: 99%
“…There are several different TBI models that utilize gyrencephalic subjects such as ferrets (Krieg et al., 2023; Schwerin et al., 2017, 2023; Whyte et al., 2019), swine (Kinder et al., 2019; Lafrenaye et al., 2015; Pavlichenko & Lafrenaye, 2023), sheep (Sharkey et al., 2023), and non‐human primates, among other species (Osier & Dixon, 2016; Vink, 2018). Common models that use gyrencephalic subjects are variations of CCI (Schwerin et al., 2017), FPI (Brodhun et al., 2001; Pavlichenko & Lafrenaye, 2023), and the CHIMERA (Krieg et al., 2023; Schwerin et al., 2023; Whyte et al., 2019). Further, another widely used large animal model is an acceleration injury model that produces DAI (Vink, 2018).…”
Section: Beyond the Rodent: Gyrencephalic Models Of Tbimentioning
confidence: 99%
“…Beyond the papers featuring rotational acceleration injury, Dr. Shin and colleagues in the Kilbaugh laboratory reported on the efficacy of a promising biological approach targeting phosphorylated tau and reducing pathology after a controlled cortical impact (CCI) in pigs [6]. Additionally, Pavlichenko and Lafrenaye employed central fluid percussion injury (CFPI) in pigs and found that while cellular signs of pathology and inflammation correlated with the pressure pulse, blood gasses and mean arterial pressure did not; furthermore, they reported that preserved, refrigerated pig brain tissue was histologically viable after 10 years [7]. We also received papers detailing new tools for use in pig neurotrauma studies.…”
mentioning
confidence: 99%